Implementation of Blended Learning using Schoology On the Topic of Invertebrate to Improve Student Learning Outcomes - Fikky Dian Roqobih; Reni Ambarwati (Universitas Negeri Surabaya, 2020)
Invertebrate is a very wide topic, that includes approximately eight phyla. Problem in teaching this topic is the limitation in time to achieve many learning indicators. The alternative efforts to overcome this problem is by implementing the blended learning. Blended learning is a kind of learning that combines face-to-face learning in the classroom and online learning that can be conducted everywhere. This study aimed to evaluate the learning process of blended learning using Schoology, student responses and students learning outcomes of invertebrate material through blended learning using Schoology. This research was conducted by involving 33 students of Grade X by using one group pre-test and post-test design. Data obtained were learning process based on lesson plan and student activities, student responses as well as students learning outcomes. Instruments used were observation sheets, responses questionnaires, as well as pretest and posttest sheets. The data of learning process and student activities were analyzed descriptive-quantitatively. Data of learning outcomes were analyzed based on learning mastery and gain score. The results of this study indicated that learning process of both face-to-face learning and online learning were very successful, students also gave very good responses to the implementation of blended learning. In addition, its proven that the implementation of blended learning can improve the student learning outcomes significantly.